ANALYSIS OF STUDENT RESPONSE TO KOJA BULOK MEDIA - Nina Agus Marvilianti; Dwi Kameluh A; Ida Putri Rarasati (JOSAR (Journal of Students Academic Research), 2019)
Based on observations and interviews conducted by researchers, students are less active in learning and learning media are still limited. Grade V students find it difficult to understand cube and beam webs. This research aims to develop Koja Bulok media. Koja Bulok media can be used as a varied learning media in mathematics in elementary school. It is hoped that Koja Bulok Media can make students more active in mathematics. This research uses Research or Development (Research and Development). The research procedure uses seven stages, namely data collection, planning, product design, product design validation, product design revisions, product trials and product revisions. The research instrument was in the form of observation sheets, a list of interview questions, and a questionnaire. Koja Bulok learning media that have been developed and tested through a validation questionnaire. The final assessment of media validation was 88.48%, subject matter experts were 88.48%, and language expert validation was 86.06%, with an average rating of 88.73% categorized as very feasible. Student response questionnaire obtained an average rating of 98.66%. This shows that Koja Bulok media is suitable for use in the mathematics learning process for fifth grade elementary school.